Sex, Gender, and Science - Hird, M. author. aut Link
XI, 197 p. 1 illus.
Keywords: In Sex, Gender and Science , Myra Hird outlines the social study of science and nature, specifically in relation to 'sex', sex 'differences' and sexuality. She examines how Western understandings of 'sex' are based less upon understanding material sex differences, than on a discourse that emphasizes sex dichotomy over sex diversity and argues for a feminist engagement with scientific debate that embraces the diversity and complexity of nature.